Faktor-Faktor Penentu Belanja Daerah Kabupaten/Kota di Provinsi Papua Barat - Marcus R. Maspaitella; Lillyani M. Orisu; Rahel Y. Tiwery (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2018)
Regional autonomy has provided a rightful authority for local governments to set and manage their own governmental affairs. The implication derived from this regulation is that local governments have to fulfill the regions’ needs as well as to explore much more potentials owned. This can enhance the capacity of local governments that could be a useful capital in financing operational programs. This research aims to analyse the influence of region own source revenue, balance fund, and other lawful local revenues on local government expenditure of regencies and city in Papua Barat province between 2010 and 2015. Sample in this research includes six regencies and one city. Panel data regression was employed to estimate the fitted model. The result indicated that the effects of balance fund and other lawful local revenues were positive and significant, whereas the influence of region own source revenue was not significant on government expenditure of regency/city in Papua Barat.